2010
DOI: 10.1002/cyto.a.20838
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumor cells in breast cancer patients utilizing multiparameter flow cytometry and assessment of the prognosis of patients in different CTCs levels

Abstract: We wanted to demonstrate the value of multiparameter flow cytometry in detecting human tumor cells of breast cancer (BC) (SKBR-3) in normal peripheral blood. In addition, we investigated a cluster of patients to compare the overall survival (OS) between advanced BC patients [circulating tumor cells (CTCs) !5 group] and limited BC patients (CTCs <5 group). SKBR-3 human BC cells were serially diluted in normal whole blood to demonstrate the sensitivity of multiparameter flow cytometry for detecting CTCs, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…To improve the chances of tumor cell detection, antibodies against intracellular melanoma tumor antigens, gp100, Mart-1, S100 and tyrosinase were pooled and detected by an indirect PE stain and combined with an APC conjugated antibody against the surface antigen MCSP. Pooling of antibodies and detecting them with multiple PMTs is consistent with a study in breast cancer, where antibodies against EpCAM and cytokeratins were labeled with PE and FITC, respectively, to detect breast cancer in blood samples (16). The pooling was performed to decrease the possibility of false-negatives (16), and we saw similar data indicating improved detection of tumors when antibodies were pooled.…”
Section: Discussionsupporting
confidence: 82%
“…To improve the chances of tumor cell detection, antibodies against intracellular melanoma tumor antigens, gp100, Mart-1, S100 and tyrosinase were pooled and detected by an indirect PE stain and combined with an APC conjugated antibody against the surface antigen MCSP. Pooling of antibodies and detecting them with multiple PMTs is consistent with a study in breast cancer, where antibodies against EpCAM and cytokeratins were labeled with PE and FITC, respectively, to detect breast cancer in blood samples (16). The pooling was performed to decrease the possibility of false-negatives (16), and we saw similar data indicating improved detection of tumors when antibodies were pooled.…”
Section: Discussionsupporting
confidence: 82%
“…The advantages of flow cytometry (FCM) are a rapid readout of routine measurements, the fact that size information is included in the data, and the capability of multicolor analysis. Several studies have independently reported flow cytometric detection and enumeration of CTC (13)(14)(15)(16). Because the detection limit of rare cells using the cytometer is approximately 10 25 (6), preenrichment and multicolor analysis of CTC will be necessary for their detection using common methods of immunofluorescence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the study model, tumor cells from the ovarian cancer cell line CaOV-3 were spiked into leukapheresates prior to separation by elutriation, and tumor cell recovery was determined by flow cytometry. Since flow cytometry has an expected resolution of one epithelial tumor cell in 10 5 nucleated cells (46,47), a spike ratio of 26 tumor cells per million PBMNCs ($50 tumor cells per mL of blood) was specified to ensure their detection. The large number of cells harvested by leukapheresis necessitated the physical pre-enrichment of CTCs to allow the practical use of immunological based methods for their isolation thereafter.…”
Section: Discussionmentioning
confidence: 99%